A20 and Cell Death-driven Inflammation. Issue 5 (May 2020) - Priem, Dario; van Loo, Geert; Bertrand, Mathieu J.M.
Abstract : A20 is a potent anti-inflammatory molecule, and mutations in TNFAIP3, the gene encoding A20, are associated with a wide panel of inflammatory pathologies, both in human and mouse. The anti-inflammatory properties of A20 are commonly attributed to its ability to suppress inflammatory NF-κB signaling by functioning as a ubiquitin-editing enzyme. However, A20 also protects cells from death, independently of NF-κB regulation, and recent work has demonstrated that cell death may drive some of the inflammatory conditions caused by A20 deficiency. Adding to the fact that the protective role of A20 does not primarily rely on its catalytic activities, these findings shed new light on A20 biology. Highlights: A20 is a ubiquitin-modulating enzyme that harbors both E3 ligase and deubiquitylase activities. In addition, it contains specialized ubiquitin-binding domains (ZnF domains) to regulate innate immune signaling pathways. Mutations in TNFAIP3, the gene encoding A20, are associated with various inflammatory disorders, such as Crohn's disease, systemic lupus erythematosus, rheumatoid arthritis, type 1 diabetes mellitus, psoriasis, and atherosclerosis. The anti-inflammatory properties of A20 were long attributed to its ability to inhibit NF-κB signaling. Recent studies in the mouse demonstrate that A20 indirectly prevents pathological inflammation by inhibiting cell death. A20 protects cells from apoptosis, necroptosis, pyroptosis, or a combination of these cell death modalities, depending on the cellular context. To protect cells from death, A20 can combine both its catalytic and nonenzymatic activities.